Pelatihan Pembuatan Sistem Informasi Kelurahan untuk Meningkatkan Layanan Publik di Kelurahan Anreapi, Polman, Sulawesi Barat: Workshop in Providing Kelurahan Information System to Enhance Public Services in Anreapi, Polman, Sulawesi Barat - Seppewali, Andi; Syahrir, Nur Hilal A (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Kelurahan is a form of local government in Indonesia which act as a servant in sub-district level. As an administrative unit of government, especially for the sub-district level, Kelurahan is responsible for providing various public services which are directly useful to the local community. One of the public services provided by the kelurahan includes residential administration. Our PkM team conducted workshop in establishing information systems to improve public services in Kelurahan Anreapi, Polman, Sulawesi Barat. The activity consists of three stages. The first stage is the preparation of workshop, ie. Searching platforms for information system, registrating the domain, and creating the website. The second stage is the workshop activity, and the third is evaluation of workshop’s activity. This activity significantly impacts accelerating participants' knowledge and skills regarding the information systems.